2012
DOI: 10.1097/sla.0b013e3182331870
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Virulence Expression Is Directly Activated by Morphine and Is Capable of Causing Lethal Gut-Derived Sepsis in Mice During Chronic Morphine Administration

Abstract: OBJECTIVE This study was designed to examine the effect of morphine administration on the intestinal mucus barrier and determine its direct effect on the virulence and lethality of Pseudomonas aeruginosa, one of the most frequent pathogens to colonize the gut of critically ill patients. SUMMARY BACKGROUND DATA Surgical injury is associated with significant exposure of host tissues to morphine from both endogenous release as well as its use as a potent analgesic agent. Morphine use in surgical patients expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 43 publications
0
70
0
2
Order By: Relevance
“…The intestinal epithelium is composed of rapidly proliferating cells, and is therefore susceptible to Cy. This results in destruction of mucosal barrier and translocation of intestinal microbiota [25] [26]. In this study, the RT-PCR and PCR-DGGE results showed that Cy caused an imbalance in gut microbiota, including decreased abundance of Bifidobacterium, reduced diversity, and altered microflora composition.…”
Section: Discussionmentioning
confidence: 87%
“…The intestinal epithelium is composed of rapidly proliferating cells, and is therefore susceptible to Cy. This results in destruction of mucosal barrier and translocation of intestinal microbiota [25] [26]. In this study, the RT-PCR and PCR-DGGE results showed that Cy caused an imbalance in gut microbiota, including decreased abundance of Bifidobacterium, reduced diversity, and altered microflora composition.…”
Section: Discussionmentioning
confidence: 87%
“…We have recently shown by 16SrRNA analysis and culture, that the gut of critically ill septic patients undergoes a nearly complete ecologic collapse with emergence of ultra-low diversity pathogen communities of two to four multi-drug resistant healthcare associated pathogens [35]. These pathogens can express virulence in response to host factors such as inorganic phosphate depletion or the release of opioids which are known to transduce the virulence circuitry of highly problematic bacteria such as Pseudomonas aeruginosa [20]. Our laboratory has shown that limitations of phosphate availability in the intestine results in induction of P. aeruginosa and other pathogens to express a lethal phenotype by triggering phosphosensory and regulatory pathways that connect directly to virulence pathways that in turn become activated [38].…”
Section: The Disappearing Microbiome and Its Replacement By A Pathobimentioning
confidence: 99%
“…Stressors such as hypotension, opioids hypoxia, ischemia, gut starvation, or reductions in gut motility from opioids upregulate genes responsible for the expression of endotoxin-A and pa-1. 149 , 150 These changes increase the ability of the bacteria to attach to mucosal cells and render them more toxic. When these activated bacteria were induced prior to injury, mortality rates of the injured animals increased.…”
Section: Organ-specific Inflammatory Responses Of the Acquired Immunementioning
confidence: 99%